Airway responsiveness to histamine and methacholine: relationship to minimum treatment to control symptoms of asthma. Issue 8 (August 1981) - Juniper, E F; Frith, P A; Hargreave, F E
Abstract : We have prospectively examined in 51 patients the relationship between the level of airway responsiveness to histamine and methacholine and the minimum medications required to control asthma. First we determined the least medication that was required to control symptoms so that they did not disturb sleep, were not present on waking, and did not require use of inhaled salbutamol (200 microgram) more than four times daily. When baseline FEV1 was greater than 70% of predicted and when there had been no respiratory infection or allergen exposure for six weeks, histamine and methacholine inhalation tests were carried out on separate days to determine the provocation concentration causing a fall in FEV1 of 20% (PC20). There was a close correlation between the PC20 to the two agents. The patients were grouped into 1, those who required no medication; 2, those who required salbutamol (200 microgram) occasionally but not daily; 3, those who required daily salbutamol; and 4, those who required additional beclomethasone dipropionate. The mean PC20 was highest in group 1 and lowest in group 4; there was a significant difference between each group. The results indicate that airway responsiveness to vasoactive amines is either an important determinant of the severity of asthma and the medication requirements or a consequence of the severity of asthma. They raise the possibility that measurement of responsiveness may be useful in some patients with established asthma to substantiate or question medication needs.